A practical guide to interpreting and applying systematic reviews of qualitative studies in rheumatology. (5th November 2020) - Sumpton, Daniel; Kelly, Ayano; Tunnicliffe, David; Craig, Jonathan C.; Guha, Chandana; Hassett, Geraldine; Tong, Allison
Abstract: While patient‐centered care is widely advocated in the management of rheumatic diseases, it can be challenging to implement, particularly for patients with complex systemic conditions. Patient‐centered care involves identifying and integrating the patient's experiences, attitudes, and preferences in decision‐making. Qualitative research is used to describe patient perspectives and priorities that may not always be expressed in clinical settings. Systematic reviews of qualitative studies can provide new and more comprehensive evidence of patients' beliefs and priorities across different populations and healthcare settings and are increasingly being reported across medical specialties, including rheumatology. In rheumatology, they have been used to examine topics including medication‐taking and adherence, coping with systemic sclerosis and conservative management and exercise in osteoarthritis. By referencing recent examples of systematic qualitative reviews in the rheumatology literature, this article will outline the methodology and methods used, and provide an approach to guide the appraisal of reviews. We aim to give the reader a practical understanding of systematic reviews of qualitative literature and elucidate how knowledge gained from such reviews can be applied to improve the care of patients with rheumatic conditions.